Chronic idiopathic neutropenia: A periodontist's diagnosis - Subash Chandra Raj; Annuroopa Mahapatra; Poonam Agrawal; Kaushik Patnaik; Shib Shankar Pradhan (Wolters Kluwer Medknow Publications, 2020)
Our aim is to report the periodontal findings of a 10-year-old boy who visited the outpatient department of periodontology, with the chief complaint of swelling in the right cheek region for the last 2 months, increasing mobility of the teeth, and frequent bleeding from the gums. Since the age of 4 years, he suffered from recurrent febrile episodes, with boils and furuncles on the face. After several hematological and immunological investigations, he was diagnosed with chronic idiopathic neutropenia. He was prescribed a 150 μg subcutaneous injection of recombinant granulocyte colony-stimulating factor, once daily for 8 days. For reducing oral inflammation, he was advised an oral rinse of 15 ml of chlorhexidine gluconate (0.12%) twice daily and advised for a routine periodontal checkup, every 3-4 weeks for evaluation, maintenance, and avoiding any acute inflammatory flare-ups.